Lossless audio compression based on a new prediction method and Golomb-Rice coding - Putong, Arnold M. (2001)
We present a scheme for compressing audio data losslessly. The compressor consists of two major parts : a new prediction method that runs in linear time and a residual coder based on Golomb-Rice coding. We show that the compression ratios produced by this scheme is comparable to those of the best publicly available compressors.